2009
DOI: 10.1364/oe.17.012493
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz near-field enhancement in narrow rectangular apertures on metal film

Abstract: We report huge field accumulations in rectangular aperture arrays on thin metal film by using shape resonance in THz frequency region. A huge far-field transmission enhancement is observed in samples of various widths ranging from 10 mum to 1.8 mum which correspond to only an order of lambda/100. Theoretical calculations based on vector diffraction theory indicates 230 times near-field enhancement in case of the 1.8 mum wide rectangular aperture. Transmission measurement through the single rectangular aperture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…(13) for infinitely large periods P. The inverse frequency dependence for a single slit well known from the literature 15,16,20,24 is clearly noticed. The geometric parameters w and h enter not only to the explicitly written arctangent function but also to the quantityc ¼ c þ c 0 (remember that c 0 is defined by Eq.…”
Section: Microscopic Model a Field Enhancementmentioning
confidence: 62%
See 1 more Smart Citation
“…(13) for infinitely large periods P. The inverse frequency dependence for a single slit well known from the literature 15,16,20,24 is clearly noticed. The geometric parameters w and h enter not only to the explicitly written arctangent function but also to the quantityc ¼ c þ c 0 (remember that c 0 is defined by Eq.…”
Section: Microscopic Model a Field Enhancementmentioning
confidence: 62%
“…[15][16][17][18][19] Park et al 19 observed a 170-fold field enhancement through an array of slits studied in terms of broadband filtering; an enhancement of about 430 was expected in the near field of periodic rectangular slits. 18 At THz frequencies, bulk 20-100 nm thick metal films become non-transparent and reflects most of the incident radiation (in the visible 20 nm, film can transmit up to 50%).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the field inside the holes does not experience a strong decay, photons spend a long time in the system, and transmission resonances can eventually take place. Recent numerical studies and experiments of near-field enhancement [17][18][19] and enhanced transmission [20][21][22] have shown unexpected redshifts of the near field and transmission features compared to λ c . These works consider either isolated holes or arrays of apertures combined with dielectric substrates and are developed in the terahertz (THz) and optical regimes.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)) [3][4][5]. Here, both reflected wave and transmitted wave are assumed as a summation of diffracted waves, and the electromagnetic field inside the slit is expanded following a cavity mode with open boundary condition.…”
Section: Theory Model and Emi Shielding Breaching In DC Limitmentioning
confidence: 99%